2017
DOI: 10.1098/rsbl.2017.0254
|View full text |Cite
|
Sign up to set email alerts
|

Possible co-option ofengrailedduring brachiopod and mollusc shell development

Abstract: In molluscs, two homeobox genes, () and (), are transcription factors that are expressed in correlation with shell development. They are expressed in the regions between shell-forming and non-shell-forming cells, likely defining the boundaries of shell-forming fields. Here we investigate the expression of two transcription factors in the brachiopod We find that is expressed in larval mantle lobes, whereas is expressed in larval tentacles. We also demonstrate that the embryonic shell marker mantle peroxidase ()… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The gene expression patterns we observed indicate that the two main groups of lophotrochozoan biomineralisers, brachiopods and molluscs, base their shell formation on a shared and conserved genetic foundation. Of the studied genes, en is arguably the most implicated in shell development in both groups [48,66] and as demonstrated here en was clearly and exclusively expressed in the T. transversa mantle margin, which indicates its involvement in shell formation due to the vicinity of CaCO3-excreting vesicular cells. dlx was also predominately expressed in the mantle margin, with an additional expression domain in the lophophore rudiment.…”
Section: A Shared Brachiopod-mollusc Complement Of Genes Involved In ...supporting
confidence: 67%
“…The gene expression patterns we observed indicate that the two main groups of lophotrochozoan biomineralisers, brachiopods and molluscs, base their shell formation on a shared and conserved genetic foundation. Of the studied genes, en is arguably the most implicated in shell development in both groups [48,66] and as demonstrated here en was clearly and exclusively expressed in the T. transversa mantle margin, which indicates its involvement in shell formation due to the vicinity of CaCO3-excreting vesicular cells. dlx was also predominately expressed in the mantle margin, with an additional expression domain in the lophophore rudiment.…”
Section: A Shared Brachiopod-mollusc Complement Of Genes Involved In ...supporting
confidence: 67%
“…A chitin network forms at the onset of brachiopod and mollusc shell fields (Schiemann et al, 2016) and has been found to be expressed in epithelial cells of fishes and amphibians (Tang et al, 2015). Brachiopods and molluscs have also possibly independently co-optedengrailed into shell formation (Shimizu et al, 2017). Among the suite of 25 transcription factors found by Sun et al (2020) are several involved in shell matrix protein production including pif, chitin-bindingperitrophin-A domain gene, and chitin synthase.…”
Section: Skeletons and The 'Metazoan Toolkit'mentioning
confidence: 99%
“…However, different Hox genes are deployed in the shell fields of brachiopods and molluscs, suggesting they do not share an ancestral role in specification of the shell‐forming epithelium. Expression patterns of engrailed in larvae of molluscs and brachiopods show it is involved in shell formation in both phyla, but there are no conserved non‐coding sequences and a comparison of gene synteny shows significant differences in the organization of their engrailed genes (Shimizu et al, 2017), suggesting independent co‐option of engrailed for shell formation (rather than by common ancestry) in brachiopods and molluscs, at least.…”
Section: The Evidence For the Early Evolution Of Animal Skeletonsmentioning
confidence: 99%
“…Consistently, Zhang et al (2012) found that an oyster homolog of engrailed was highly expressed at early gastrula stage when shell gland formation in oysters begins. A recent study also suggests the possible co-option of engrailed during mollusc and brachiopod shell development (Shimizu, Luo, Satoh & Endo, 2017).Interestingly, Wollesen et al (2017) found that characteristic brain regionalization genes in other brain-containing animal lineages are expressed in the mantle of molluscs during development, suggesting that brain regionalization genes are co-opted into shell field patterning in molluscs. From an omics scale investigation, Herlitze, Marie, Marin, and Jackson (2018) identified 34 candidate shell-forming genes for the snail Lymnaea stagnalis, most of which are expressed in the invaginated larval shell gland of the trochophore or in cells that border it.…”
Section: Shell Formation and Evolutionmentioning
confidence: 95%